Efek Penambahan Vitamin C Terhadap Laju Pertumbuhan Spesifik Ikan Pelangi Merah (Glossolepsis incisus Weber) - Agung Setia Abadi; Anik Martinah Hariati; Ellana Sanoesi (Jurnal Airaha, 2018)
The red rainbow fish ( Glossolepsis incisus Weber ) is one of Indonesia tropical ornamental freshwater fish which has economical high value. But growth rate is to slow cause the fish rarely available in the market. The purpose of this research was to find out the effect of vitamins C on spesific growth rate of this fish. The method used was in the experimental methods with 5 treatments and 2 replications of a 2 cm and 6 cm. Dosage of vitamins C used was 0 mg/kg of feed, 500 mg/kg of feed, 1000 mg /kg of feed, 1500 mg/ kg of feed and 2000 mg/kg of feed. The result showed that the added of vitamins C is high significant of SGR, FCR and significant pH and DO on the media but does not significant whit SR and temperatur. The result showed that the vitamins C with SGR and FCR is quadratic and the best dose to obtain whit added of vtamins C 1666 mg/kg of feed on the size 2 cm and dose 1111 mg/kg of feed on the size 6 cm. The increase of SGR dependent by the increasing dosage of vitamins C as weell as FCR, but if vitamins C excessive and not according to needs will be a reduce SGR and FCR.